CMOS 2.45 GHz RF power amplifier for RFID reader - Uddin, Md. Jasim; Ibrahimy, Muhammad Ibn; Hasan , M. A.; Ali, M. A. M.; Reaz, Mamun Bin Ibne (2009)
A high linearity CMOS RF (radio frequency) power amplifier, which has the advantage of being low-cost and easily integrated on chip has become the technology of choice for RFID readers. This work demonstrates a 3.3V single voltage self-biased 2.4GHz--2.5GHz high linearity RF power amplifier for RFID applications.